2021
DOI: 10.3390/vaccines9030295
|View full text |Cite
|
Sign up to set email alerts
|

Low Seroprevalence of Measles-Specific IgG in Children of Three Ethnic Groups from Mexico: Influence of Age, Sex, Malnutrition and Family Size

Abstract: Background: The reemergence of measles represents a public health problem. The aim of the study was to determine the seroprevalence of IgG antibodies against measles in children of three ethnic groups in southern Mexico and the nutritional status and demographic risk factors associated. Methods: A cross-sectional study in 416 school-age children, 207 belonging to the Tlapaneco ethnic group, 101 to the Mixteco group and 108 were considered Mestizo. Sociodemographic data were collected, an anthropometric evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Similar measles seronegativity data were also observed in children by other authors, including Gupta et al [ 23 ], where 60% of children between 5 and 10 years of age in India lacked protective immunity against measles, and Sánchez-Alemán et al [ 24 ], where 59% of Mexican children aged 6–13 years of age lacked MeV antibodies. Data reported by the WHO indicate that measles immunization coverage in the Americas has been approximately 69.2% over the past 20 years, with rates slightly higher after 2014; rates well below the threshold of herd immunity.…”
Section: Discussionsupporting
confidence: 84%
“…Similar measles seronegativity data were also observed in children by other authors, including Gupta et al [ 23 ], where 60% of children between 5 and 10 years of age in India lacked protective immunity against measles, and Sánchez-Alemán et al [ 24 ], where 59% of Mexican children aged 6–13 years of age lacked MeV antibodies. Data reported by the WHO indicate that measles immunization coverage in the Americas has been approximately 69.2% over the past 20 years, with rates slightly higher after 2014; rates well below the threshold of herd immunity.…”
Section: Discussionsupporting
confidence: 84%
“…Our study showed that older age and an uncertain history of measles vaccination were associated with a lower measles seropositivity rate. Published studies in China and Mexico also reported that lower measles seropositivity rates were associated with older age [21,22]. In terms of seroprevalence of MMR, the lower measles seropositivity found in this study is comparable to the previous study, which found that rubella and mumps seropositivity levels were lower among adolescents [23,24].…”
Section: Discussionsupporting
confidence: 79%
“…35 Several studies have also found a discrepancy between ethnicity and measles infection. [36][37][38] A study showed that ethnicity and cultural background were strong predictors of MMR vaccine uptake. 36 These findings differed from our own, in that we found no link between ethnicity and laboratory-confirmed measles.…”
Section: Discussionmentioning
confidence: 99%